Pengembangan LKPD Berbasis Online Pada Mata Pelajaran Akuntansi Dasar Di SMK Ketintang Surabaya - Rizka Imas Virgianti; Agung Listiadi (Jurnal Pendidikan Akuntansi (JPAK), 2021)
This need for teaching materials used by students to suport distance learning. This study aims to create and develop student worksheets on basic accounting subjects at Vocational High School Ketintang Surabaya ; Analyzing the feasibility of student worksheets developed based on the results of validation by some experts; and knowing students responses student to worksheets. This type of research used a 4-D development model from Thiagarajan. In making this student worksheet, only use 3 stage namly define, design, and develop. The trial was on this worksheet is 20 students of class X accounting 1 Vocational High School Ketintang Surabaya. Data collection techniques using study sheets, validation sheets,and students’ responses questionnaire.The results showed that the student worksheet are declared very feasible based on the feasibility of the content, the feasibility of presentation, the feasibility of the language and the feasibility of graphics. The results of the students' responses to the criteria are very understanding. Because this student worksheet can motivate students, it is developed according to the abilities of students, the language in this worksheet can be understood and has an attractive design.